2007
DOI: 10.1103/physrevb.76.033201
|View full text |Cite
|
Sign up to set email alerts
|

Lattice site investigation of F in preamorphized Si

Abstract: The lattice location of F atoms in Si was experimentally studied. Si single crystals were amorphized, implanted with F, and afterwards the amorphous layer was recrystallized. Some of the samples prepared in this way were also annealed at 750°C for 60 min. The 19 F͑p , ␣␥͒ 16O resonant nuclear reaction at 340.5 keV was employed to measure the probability of a close encounter between protons and F nuclei as a function of the incident angle with respect to six major crystalline directions. The predictions of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In particular, simulation studies suggested that the most abundant F n V m clusters are those in which all the V dangling bonds are saturated by F. 16 Interestingly, recent experimental work 10 on F-implanted preamorphized Si determined that the predicted F n V m clusters do not exist in detectable concentrations. Nevertheless, that study 10 is consistent with theoretical work 14 as F implantation can effectively suppress the transient-enhanced selfinterstitial mediated diffusion of acceptor atoms such as B.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, simulation studies suggested that the most abundant F n V m clusters are those in which all the V dangling bonds are saturated by F. 16 Interestingly, recent experimental work 10 on F-implanted preamorphized Si determined that the predicted F n V m clusters do not exist in detectable concentrations. Nevertheless, that study 10 is consistent with theoretical work 14 as F implantation can effectively suppress the transient-enhanced selfinterstitial mediated diffusion of acceptor atoms such as B.…”
Section: Introductionsupporting
confidence: 89%
“…A number of experimental [9][10][11] and theoretical [12][13][14][15][16][17] studies address the issue of doping Si with F. These provide evidence that F n V m clusters are stable in Si. In particular, simulation studies suggested that the most abundant F n V m clusters are those in which all the V dangling bonds are saturated by F. 16 Interestingly, recent experimental work 10 on F-implanted preamorphized Si determined that the predicted F n V m clusters do not exist in detectable concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) and experimental studies consistently revealed that isovalent codoping and double donor doping in Ge do not effectively reduce the formation of dopant-vacancy clusters that can lead to deactivation [63,64]. The introduction of fluorine in Si and Ge is motivated as it is a dopant that can passivate the dangling bonds formed by the vacancies [65][66][67][68][69][70]. The key is the high electronegativity of F and via the saturation of the dangling bonds, and it essentially immobilizes the lattice vacancies.…”
Section: Fluorine Doping In Germaniummentioning
confidence: 99%
“…Codoping in semiconductor materials is an efficient way to control the diffusion of dopants and control their electrical activation [1][2][3][4][5][6]. One of the most important materials where codoping strategies have been applied is Si [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important materials where codoping strategies have been applied is Si [1][2][3][4][5][6][7][8][9][10][11][12]. F atoms in Si saturate the dangling bonds of vacancies resulting in the formation of F n V m clusters, which in turn suppress the transient enhanced diffusion of B (Refs.…”
Section: Introductionmentioning
confidence: 99%